Case report: Bilateral globus pallidus lesions and delayed progressive leukoencephalopathy in COVID-19: Effects of hypoxia alone or combination of hypoxia and inflammation? - Ballout, Ahmad A.; Kolesnik, Michael; Choi, Yuna; Ayoub, Marc S.; Harel, Asaff; Najjar, Souhel (Frontiers in Neurology, 2023)
Background The globus pallidus is a highly mitochondria-rich metabolic structure that is particularly sensitive to metabolic disturbances and hypoxia. Symmetric lesions of globus pallidus and delayed diffuse leukoencephalopathy were documented in toxic–metabolic disorders, hypoxia, a neurodegenerative disorder, and mitochondrial encephalopathies. Similar changes are also reported in individuals with active COVID-19 infections with associated hypoxia or critical illness. Case information We describe a patient with post–COVID-19 infection who presented with rapid cognitive and neurological decline associated with similar neuroimaging structural changes but without toxic–metabolic changes or hypoxia. Despite multiple non-inflammatory cerebrospinal fluid studies, mechanisms involving post–COVID-19 inflammation and immune dysregulation are suspected, given the unexplained continued decline in the neurological status, lack of concurrent hypoxia or antecedent respiratory difficulties, and after a reasonable exclusion of alternative etiologies. Hypermetabolism of both anteromedial temporal structures and diffuse hypometabolism predominantly in the frontal region on PET scan provided indirect support for possible inflammatory mechanisms after reasonable exclusion of alternative etiologies, such as direct CNS infection, among others. The patient's neurological impairment improved substantially after treatment with pulse steroids, plasmapheresis, and rituximab. Conclusion To the best of our knowledge, this is the first report of post–COVID-19 with bilateral symmetric contrast-enhancing necrotic lesions of globus pallidus with delayed diffuse supratentorial leukoencephalopathy with microhemorrhages without concurrent hypoxia or reported preceding symptoms suggestive of hypoxia. We suspect that these inflammatory mechanisms might be triggered by prior COVID-19 exposure/infection. Furthermore, the role of the cross-talk between inflammation and clinically mild or silent hypoxia linked to prior COVID-19 infection cannot be excluded. Awareness of these post–COVID-19 neurological sequelae and their potential pathophysiology among those with no known antecedent significant hypoxia are important for early recognition and treatment.